Identifying time trends in advertising expenditure components - Košmelj, Katarina (Metodološki zvezki, 2009)
The study analyzes the components of advertising spending for a group of European countries with stable total advertising spending over the period 1994-2007. Three components of advertising spending were considered: Electronic, Print, and Online. Our main objective was to study how the components were restructured within the period under study and to find clusters of similar countries. A specific distance for time series, which is expressed as a linear combination of a standard distance measure and the weights, was to be used. The standard distance used for compositional data is the Aitchison distance, however it was found unsuitable due to zero and near zero values in the Online component. As a simple alternative a linear regression model on the components was used, followed by standard cluster analysis on the regression estimates. Results enable a deeper insight into the level of each component and into the structural changes in components for clusters of examined countries.
Keywords: Europe; Evropa; oglaševanje; advertising; stroški; trendi; statistične metode; časovne vrste; analiza